Dynamic capabilities, knowledge management, and lecturer performance as determinants of health workers' readiness in health services - Tarjuman, Tarjuman; Ahman, Eeng; Suryadi, Edi; Askolani, Askolani (Poltekkes Kemenkes Bandung, 2026)
Background: Higher education institutions play a strategic role in preparing competent healthcare professionals and ensuring the quality of health services in the community. In the era of rapid health system transformation and technological advancement, health polytechnics are required to strengthen organizational performance through effective knowledge management, lecturer competence, and motivation to support adaptive institutional capabilities. Objective: This study examined the effects of knowledge management, lecturer motivation, and lecturer competence on the institutional performance of Health Polytechnics. Methods: Using an explanatory quantitative design, data were collected from 380 lecturers at 38 institutions through stratified sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The results indicate that all independent variables significantly influence institutional performance. Organizational dynamic capabilities and lecturer performance are proven to act as significant mediators, both in parallel and serial relationships. A crucial finding indicates that the serial mediation pathway of knowledge management through dynamic capabilities and lecturer performance has the strongest influence. This confirms that the transformation of knowledge into organizational adaptive capabilities significantly determines institutional effectiveness. Conclusions: This research indicates that strengthening lecturer capacity is essential for producing graduates who are adaptive to digital transformation and modern healthcare systems. Practically, this study provides strategic guidance for human resource development in higher health education to improve public health services sustainably.